IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA PERBANKAN SYARI’AH DI INDONESIA - Setyani, Nur Hidayati (Economica: Jurnal Ekonomi Islam, 2012)
Bank is financial institution, which is a fungtioning financial intermediary from two parties, namely sides that excess fund and poor one party lents fund. Principle syari’ah is ruling indentured base islamic law among bank and party othering to keep fund and/or business activity finanance, or stated another activity according to syari’ah.Good corporate governance (GCG) is manner brings of bank that are principles apply; transparency , accountability, responsibility, independency and fairness. GCG’s principles really back up syar’i. In Islam also recognized many muamalah’s principles as; justice, tazawun, masuliyah, behaviour, shiddiq, trust ,fathanah , tabligh hurriyah, charity, wasathan, ghirah, idarah, khalifah, aqidah , ijabiyah, raqabah, qira’ah and islah. Implementation  about performing GCG at various institute carries on business to get profit’s orientation, notably financial institution/syari’ah bank, constitute a certainty, even syari’ah’s financial institutions in particular bank syari’ah, ought to becomes pionir, since to carried on terminological islamic principles.